External breast prostheses after mastectomy: production and selection of a low-cost functional model to be performed in developing countries - Vieira, René Aloisio da Costa; Ibrahim, Matheus Sampaio; de Souza Araujo, Lucas Guimarães; Souza Junior, José de Assis e; de Freitas, Carla Simone Moreira; de Oliveira, Luiz Carlos Navarro (Frontiers in Oncology, 2024)
Introduction: Breast cancer is one of the most common types of cancer affecting women. Despite advancements in early diagnosis, neoadjuvant therapy, and various treatment modalities, mastectomy remains a common procedure for many women. Although some women opt for reconstructive surgery (BR), many do not have the indication, desire, or opportunity to undergo this procedure. Methods: An easily manufactured, washable, lightweight, and inexpensive external breast prosthesis (EBP) model was developed specifically for the study. Participants were presented with five EBP models–one commercially available, three manufactured options, and one created for the study–and were asked to choose a prosthesis. We also evaluated the factors associated with non-adherence to EBP among women who had undergone mastectomy without BR. The chi-square test was used to assess adherence or non-adherence to EBP, while logistic regression was used to identify factors associated with non-adherence. Results: We introduced a low-cost, lightweight, washable EBP model. When participants were asked to choose between two prostheses, the silicone prosthesis was the first choice for 33.9% of the participants, while the prosthesis created for the study emerged as the second choice for 70.5%. Out of the 72 women assessed, 45.8% (33) opted not to use any of the EBP models. Our analysis revealed that age and BMI were significantly associated with non-use of EBP. Conclusion: Multiple barriers contribute to non-adherence to EBP, underscoring the need for interventions aimed at improving patient knowledge and adherence. This study introduces a lightweight, easily reproducible, and low-cost EBP model.